2011
DOI: 10.1017/jfm.2011.150
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of evolution of the propeller wake in the transition and far fields

Abstract: In the present study the mechanisms of evolution of propeller tip and hub\ud vortices in the transitional region and the far field are investigated experimentally.\ud The experiments involved detailed time-resolved visualizations and velocimetry\ud measurements and were aimed at examining the effect of the spiral-to-spiral distance\ud on the mechanisms of wake evolution and instability transition. In this regard, three\ud propellers having the same blade geometry but different number of blades were\ud consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
250
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(290 citation statements)
references
References 32 publications
39
250
1
Order By: Relevance
“…The flow visualization using snowflakes evidences that the pairing and merging of two or three adjacent tip vortices and the collapse of vortices occur frequently within a half rotor diameter (that is, x/D ¼ 0.5) downstream of the turbine blades. Although the grouping of tip vortices has been observed in a number of prior studies 23,28 , it was reported to appear much farther downstream of the turbine when compared with that in our study. By correlating the visualized vortex structures with the synchronized turbine performance information, our experiment has shown some connection between the vortex interactions and subtle changes in the turbine operation.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The flow visualization using snowflakes evidences that the pairing and merging of two or three adjacent tip vortices and the collapse of vortices occur frequently within a half rotor diameter (that is, x/D ¼ 0.5) downstream of the turbine blades. Although the grouping of tip vortices has been observed in a number of prior studies 23,28 , it was reported to appear much farther downstream of the turbine when compared with that in our study. By correlating the visualized vortex structures with the synchronized turbine performance information, our experiment has shown some connection between the vortex interactions and subtle changes in the turbine operation.…”
Section: Discussioncontrasting
confidence: 56%
“…The characteristics of vortex interaction observed in our study would imply a fast dissipation of wake structures and significantly different wake growth for a utility-scale turbine. For example, the 'multi-step' tip-vortex grouping mechanism reported in Felli et al 28 and the interactions of tip vortices and the hub vortex 22,23 may manifest very differently for utility-scale turbines. All these issues pose important questions that will form the basis of future investigations, which will integrate the SLPIV technique with high-fidelity numerical simulations.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison between a WT wake and an AD wake in the presence of leapfrogging is for this reason of particular interest. Following the experimental studies of Dobrev et al (2008), Felli et al (2011), andSherry et al (2010), Lignarolo et al (2014a) have shown how the instability of the tip-vortex helix has a major effect on the wake mixing and re-energising mechanism. Lignarolo et al (2015a) have conducted a detailed analysis of the effect on the turbulence field and wake mixing due to the presence of the leapfrogging instability.…”
mentioning
confidence: 89%
“…As before, no breakdown is observed; the vortices remain concentrated and intact. Systems of two or more interlaced helical vortices, such as the ones generated by multi-bladed rotors, may exhibit a combination of unstable modes, involving local and uniform pairing (see, e.g., the simulations by Ivanell et al [9] and the experiments by Felli et al [10]). The resulting deformations may have quite a complicated structure, but as long as the associated wavelengths are large compared to the vortex core size, they can in general always be linked to some type of pairing mechanism, due to the mutual induction between the different parts of the wake vortices.…”
Section: Long-wave Instabilitiesmentioning
confidence: 99%